STUDI ANALISIS EFEK SAMPING KEMOTERAPI PADA PASIEN KANKER PAYUDARA DI RSUD DR. H. ABDUL MOELOEK PROVINSI LAMPUNG TAHUN 2023: STUDY ANALYSIS OF SIDE EFFECTS OF CHEMOTHERAPY IN BREAST CANCER PATIENTS AT DR. H. ABDUL MOELOEK LAMPUNG PROVINCE YEAR 2023 - Widiyastuti, Asih; Handayani, Kartika; Harissa, Nola; Wahidah, Lilik Koernia; Nopiyansyah (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2025)
The high mortality rate in breast cancer and with the most malignancy attacking women, therapy is needed in the treatment of breast cancer by chemotherapy. Chemotherapy works by killing rapidly dividing cancer cells. However, due to its non-selective nature, chemotherapy also affects healthy cells and causes side effects that affect the patient's quality of life. This study aims to determine the side effects of chemotherapy in breast cancer patients at Dr. H. Abdul Moeloek Hospital, Lampung Province in 2023. This type of research is a qualitative descriptive observational study with a cross-sectional design and accidental sampling data collection techniques. Data analysis was done descriptively in the form of a percentage. The sample in this study was 41 patients. The results of the study based on the characteristics of female gender were 41 patients (100%) and male patients were 0 patients (0%), the age of the diagnosed patients was in the age range of 36-45 years as many as 13 patients (31.7%), 46-55 years as many as 13 patients (31.7%), and 56-65 years as many as 13 patients (13.7%), based on the patient's occupation with the occupation of a housewife (IRT) as many as 24 patients (58.5%), treatment with the TdCar regimen (Taxane (docetaxel), Carboplatin) as many as 13 patients (26.9%) and the AC regimen (Doxorubicin, Cyclophosphamide) as many as 11 patients (21.2%). The conclusion of this study is the side effects using the Naranjo algorithm, the score obtained is between 1-4 (possible) which means that there may be an ADR. The most common side effects suffered by breast cancer chemotherapy patients at Dr. Soetomo Hospital. H. Abdul Moeloek Lampung Province in 2023 was hair loss (87.8%). Keywords: Side Effects, Breast Cancer, Chemotherapy, Cross-sectional